1997
DOI: 10.1007/s004390050611
|View full text |Cite
|
Sign up to set email alerts
|

No founder effect detected in Jewish Ashkenazi patients with fragile-X syndrome

Abstract: Several studies on small homogenous populations suggested that fragile-X syndrome originated from a limited number of founder chromosomes. The Israeli Jewish population could serve as an adequate model for tracing a founder effect due to the unique ethnic makeup and traditional lifestyle. Furthermore, a common haplotype for Jewish Tunisian fragile X patients was recently reported. To test for a similar occurrence in the Jewish Ashkenazi population, we performed haplotype analysis of 23 fragile-X patients and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
1
7
1
Order By: Relevance
“…Our ®ndings apparently contrast with most other reports on FXS founder effects in different ethnic groups [Richards et al, 1992Jacobs et al, 1993;Buyle et al, 1993;Hirst et al, 1993;Haataja et al, 1994;Macpherson et al, 1994;Zhong et al, 1994aZhong et al, , 1994bZhong et al, , 1996aZhong et al, , 1999Syrrou et al, 1996;Chiurazzi et al, 1996aChiurazzi et al, , 1996bChiurazzi et al, , 1996cFalik-Zaccai et al, 1997;Bonaventure et al, 1998;Pekarõ Ák et al, 1999;Mingroni-Netto et al, 1999]. There was only one report [Pesso et al, 1997] showing no founder effects in a speci®c ethnic population, that of Ashkenazi Jews. Falik-Zaccai et al [1997] showed, however, that Tunisian Jews have a rare founder haplotype.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Our ®ndings apparently contrast with most other reports on FXS founder effects in different ethnic groups [Richards et al, 1992Jacobs et al, 1993;Buyle et al, 1993;Hirst et al, 1993;Haataja et al, 1994;Macpherson et al, 1994;Zhong et al, 1994aZhong et al, , 1994bZhong et al, , 1996aZhong et al, , 1999Syrrou et al, 1996;Chiurazzi et al, 1996aChiurazzi et al, , 1996bChiurazzi et al, , 1996cFalik-Zaccai et al, 1997;Bonaventure et al, 1998;Pekarõ Ák et al, 1999;Mingroni-Netto et al, 1999]. There was only one report [Pesso et al, 1997] showing no founder effects in a speci®c ethnic population, that of Ashkenazi Jews. Falik-Zaccai et al [1997] showed, however, that Tunisian Jews have a rare founder haplotype.…”
Section: Discussioncontrasting
confidence: 95%
“…In our experience, approximately 7% of Thai samples referred for FXS testing show positive results on molecular analysis [Limprasert et al, 1999a]. Previous studies have investigated haplotype associations using microsatellites near the FMR1 gene in various populations: Australian [Richards et al, 1992], British [Jacobs et al, 1993;Macpherson et al, 1994], White American [Zhong et al, 1994a, Belgian±Dutch [Buyle et al, 1993, Finn [Haataja et al, 1994;Zhong et al, 1996a], Swedish [reviewed by Chiurazzi et al, 1996a], Italian [Chiurazzi et al, 1996b], Jewish [Pesso et al, 1997;Falik-Zaccai et al, 1997], Sub-Saharah African [Chiurazzi et al, 1996c], Greek±Cyprian [Syrrou et al, 1996], Czech [Pekarõ Ák et al, 1999], Argentine [Bonaventure et al, 1998], Brazilian [Mingroni-Netto et al, 1999], Japanese and Chinese [Zhong et al, 1994b;Zhong et al, 1999]. In these reports, it is apparent that although FXS chromosomes are associated with several haplotypes, only a few account for most of the total, with a distribution signi®cantly different from that of normal controls.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was considered to imply a preferential occurrence of FMR1 mutations in certain particular chromosomal backgrounds, probably due to enrichment of longer tracts of pure CGG repeats, which eventually lead to a preferential occurrence of FMR1 mutations [Kolehmainen, 1994;Eichler et al, 1996]. Reportedly in Israel, the prevalence of FXS among Tunisian Jews was tenfold higher than in Ashkenazi Jews, with a striking founder mutational effect of the FXS well demonstrated in the former but not in the latter [Falik-Zaccai et al, 1997;Pesso et al, 1997]. Therefore, we believed that the lack of founder effect of FXS in Taiwan provides a plausible explanation to the discrepancy in fragile X prevalence between Chinese in Taiwan and Central China.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, approximately 7% of Thai samples referred for FXS testing show positive results on molecular analysis [Limprasert et al, 1999a]. Previous studies have investigated haplotype associations using microsatellites near the FMR1 gene in various populations: Australian [Richards et al, 1992], British [Jacobs et al, 1993; Macpherson et al, 1994], White American [Zhong et al, 1994a, Zhong et al, 1999], Belgian–Dutch [Buyle et al, 1993, Hirst et al, 1993], Finn [Haataja et al, 1994; Zhong et al, 1996a], Swedish [reviewed by Chiurazzi et al, 1996a], Italian [Chiurazzi et al, 1996b], Jewish [Pesso et al, 1997; Falik‐Zaccai et al, 1997], Sub‐Saharah African [Chiurazzi et al, 1996c], Greek–Cyprian [Syrrou et al, 1996], Czech [Pekarìk et al, 1999], Argentine [Bonaventure et al, 1998], Brazilian [Mingroni‐Netto et al, 1999], Japanese [Richards et al, 1994] and Chinese [Zhong et al, 1994b; Zhong et al, 1999]. In these reports, it is apparent that although FXS chromosomes are associated with several haplotypes, only a few account for most of the total, with a distribution significantly different from that of normal controls.…”
Section: Introductionmentioning
confidence: 99%